Efectos No Genéticos sobre la Reproducción en Vacas Mestizas con Predominio Bos indicus en el Municipio de Arauca, Colombia (2023)
The aim of this study was to determine some non-genetic factors that affect age at first calving (AFC) and the interval between calving (CI) in dual purpose cows in the municipality of Arauca, Colombia. Records related to AFC (n=110) and CI (n=168) of cows with Bos indicus predominance were analyzed. The effect of fixed factors that were considered for EPP were: Farm (FAR: 1,2,3), season of first calving (FCS: dry, rainy), year of first calving (FCY: 1992...2011), sex of calf (CS: M,F) and for CI: FAR, season of calving interval (SCI), year of calving interval (CIY), CS and parity number (PN: 1...5). Data was analyzed using the SAS GLM procedures and for the averages comparison was used the Duncan test with a significance level of 5%. The estimated average for AFC was 1 243.6 + 160.3 days and for CI was 608.0 + 165.4 days. FAR and FCY were significant factors of variation (p<0.05) for CY, while NP and CIY were significant factors of variation (p<0.05) for CI. It is concluded that the influence of farm, year of birth, year of calving interval and parity on reproductive parameters in crossbred cows reared under the tropical conditions of Cauca, Colombia is related to technical and productive management characteristics of each farm. Besides, age at first calving and calving interval on farms under study are within the ranges considered acceptable for the production system in flooded savanna.